Application of virtual simulation technology in sports decision training: a systematic review - Yunchao, Ma; Mengyao, Ren; Xingman, Li (Frontiers in Psychology, 2023)
Introduction Sports decision-making is a complex process and plays a decisive role in sports performance. Virtual simulation technology is one of the popular sports decision making training tools. The application of virtual reality technology in sports decision making training has received widespread attention. The purpose of this study is to evaluate the scientific evidence of the application of virtual simulation technology in sports decision-making training, and summarize its application advantages and limitations. Methods The research literature databases of Web of science, PubMed, SCOPUS and Medline were searched, and the results were screened to determine the application of virtual reality technology in motion decision-making. We identified 10 articles and coded them to record the research design, research object characteristics, VR task setting, experimental intervention and research results. Results Through the review, it is found that virtual simulation technology has important value for sports decision-making training. In sports practice, virtual simulation technology can simulate sports decision-making tasks, measure and analyze athletes’ sports decision-making performance. We still need to design a more scientific virtual simulation environment for sports decision-making. In this environment, we can better use virtual simulation technology to improve sports decision-making ability.